Meta4: a web application for sharing and annotating metagenomic gene predictions using web services - Richardson, Emily J.; Escalettes, Franck; Fotheringham, Ian; Wallace, Robert J.; Watson, Mick (Frontiers in Genetics, 2013)
Whole-genome-shotgun (WGS) metagenomics experiments produce DNA sequence data from entire ecosystems, and provide a huge amount of novel information. Gene discovery projects require up-to-date information about sequence homology and domain structure for millions of predicted proteins to be presented in a simple, easy-to-use system. There is a lack of simple, open, flexible tools that allow the rapid sharing of metagenomics datasets with collaborators in a format they can easily interrogate. We present Meta4, a flexible and extensible web-application that can be used to share and annotate metagenomic gene predictions. Proteins and predicted domains are stored in a simple relational database, with a dynamic front-end which displays the results in an internet browser. Web-services are used to provide up-to-date information about the proteins from homology searches against public databases. Information about Meta4 can be found on the project website (http://www.ark-genomics.org/bioinformatics/meta4), code is available on Github (https://github.com/mw55309/meta4), a cloud image is available, and an example implementation can be seen at http://www.ark-genomics.org/tools/meta4